1964
DOI: 10.1126/science.144.3614.54
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Accumulation in the Rumen after Overfeeding with Readily Fermentable Carbohydrate

Abstract: A neutral volatile substance in ruminal contents from sheep suffering from acute indigestion due to overfeeding has been identified as ethanol. Ethanol was consistently observed in ruminal material from both cattle and sheep after they had been fed large amounts of readily fermentable carbohydrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…This is in agreement with previously reported data on ruminants (sheep) that indicate that overfeeding with wheat grain is associated with EtOH concentrations as high as 8 mM (Allison et al 1964). Kristensen et al (2007) also reported rumen EtOH concentrations above 2 mM in dairy cows fed a TMR containing *54% corn silage and *13.5% rolled barley grain.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previously reported data on ruminants (sheep) that indicate that overfeeding with wheat grain is associated with EtOH concentrations as high as 8 mM (Allison et al 1964). Kristensen et al (2007) also reported rumen EtOH concentrations above 2 mM in dairy cows fed a TMR containing *54% corn silage and *13.5% rolled barley grain.…”
Section: Discussionsupporting
confidence: 92%
“…Ørskov et al (1967) observed caproate molar proportions of up to 15 per cent and concentrations of up to 18 mM in ruminal samples from cows fed rations high in sugar and starch (21.8 per cent each on a feed dry matter basis); in these same cows, ethanol was detected within 2 h of feeding, and the authors speculated that C. kluyveri was a likely agent for caproate production, based on its known ability to couple ethanol oxidation to reductive RBO. Moomaw and Hungate (1963) and Allison et al (1964) had also observed ethanol accumulation in the rumen, but again only under conditions of feeding diets rich in concentrates. To our knowledge there are no reports of significant ethanol accumulation in ruminants fed diets high in forages or other cellulosic materials that would likely be used in a cellulosic biofuels system.…”
Section: Resultsmentioning
confidence: 87%
“…Ethanol has been identified as a transient component of rumen fluid both in vitro and in vivo, particularly when diets rich in grains are fed. Allison et al (1964) reported that 12 of 12 sheep fed cracked wheat had detectable levels of ethanol in the rumen, and in one sheep, ethanol concentrations reached 33 mM (although this sheep died a few hours later). Dietary induction of ethanol accumulation has been reported to increase butyrate and caproate concentrations in the rumen, with the latter reaching up to (Ørskov et al 1967).…”
Section: Discussionmentioning
confidence: 96%